(untitled) (Práxis Educativa, 2017)
This study, originated from a PhD thesis and aims at analyzing Brazilian and French Maths teachers’ social representations of their professional competence. The analysis is based on a theoretical survey of the relation between the terms profession and professionalism and elements related to the skills and features of teachers’ professionalism (ABAELLA, 1992; ROLDÃO, 2005, among others). The methodology is based on the Central Nucleus Approach (ABRIC, 1976). The research comprised 252 Brazilian and French teachers of Mathematics working in public schools. Among the results, we highlight the similarities and differences between teachers’ representations of their professional competence, based on the domains of ethics, subject taught, teaching methods, personality, among others, of the teacher professionalism. Keywords: Profissionalism. Teacher. Social Representations. Maths teachers’ professional competence.